PROFILKEMAMPUANSISWADIFKIPUNIVERSITASRIAUPADAPELAKSANAANPEMBELAJARANMATEMATIKAPADA PPL DISMA/SMKPEKANBARU (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis study was a descriptive study which aimed to obtain the representation of studentâs ability in FKIP Riau University on implementing mathematics learning. This study was conducted on odd semester academic year 2014/2015. The subjects were the students in Mathematics Education totaling 27 students which following field practice in 7 senior high school and3vocationalhigh schoolinPekanbaru. The data were collected by observing the studentâs learning activity and interviewing with students, teachers, and learners. The data were analyzed by using descriptive technique. The result showed that the students in FKIP Riau University had a good ability on implementing mathematics learning. The ability of students was in the interval 3,85â4,13 (scale 1-5) based 12 ability aspects which has been observed. The lowest ability of students was the ability which using approach/model/strategy/method of learning, while the highest ability was the ability which using communicative language.Keywords: The ability on implementing mathematics learning, field practice, the students in FKIP Riau University